Optimalisasi Stand-Alone Photovoltaic System dengan Implementasi Algoritma P&O-Fuzzy MPPT - Juniyanto, Dimas; Andrasto, Tatyantoro; Suryono, Suryono (Jurnal Teknik Elektro, 2018)
The need for electrical energy continues to increase every time. Concerns about the depletion of fossil energy reserves encourage the acceleration of the development of renewable energy use. One of renewable energy is the solar energy. Due to the irreversible irradiation conditions, it takes controls to keep the solar panel's maximum power. The most widely in Maximum Power Point Tracking (MMPT) is Perturb Algorithm and Observe (P&O) but P&O Algorithm has deficiency of oscillations when steady state and MPP trace errors when irradiation changes rapidly. In this paper proposed P & O-Fuzzy algorithm is a modification of conventional P & O to improve the efficiency of solar panels. This research uses Matlab for simulation and hardware implementation using microcontroller Arduino Uno and buck converter topology. The result of simulation and hardware implementation, conventional P & O has an average efficiency of 85.03% while MPPT modification with P & O-Fuzzy algorithm can improve MPP tracking efficiency with 89.67%.